Gender Differences in the Response to Impaired Sleep in Adults with Diabetes - Chasens, Eileen R. (Behav Sleep Med, 2015)
This study analyzed cross-sectional data to examine gender differences in the association of sleep quality and daytime sleepiness with mood and functional outcomes in adults with type 2 diabetes (T2DM). Measures included demographic and clinical data as well as scales that measured subjective daytime sleepiness, sleep quality, mood disturbances, and functional outcomes. The majority of the sample (N = 116) had poor sleep quality and was subjectively sleepy. We observed in males and females significantly different associative patterns between the predictor variables of daytime sleepiness and sleep quality and the outcome variables of mood and functional outcomes. There was no significant difference in daytime sleepiness or impaired sleep quality between men and women with T2DM; however, there was a difference in the expression of impaired sleep on mood and functional outcomes between genders.